Basic Properties of High-Dynamic Beam Shaping with Coherent Combining of High-Power Laser Beams for Materials Processing - Rudolf Weber; Jonas Wagner; Alexander Peter; Christian Hagenlocher; Ami Spira; Benayahu Urbach; Eyal Shekel; Yaniv Vidne (Journal of Manufacturing and Materials Processing)
Lasers with average powers of several kilowatts have become an important tool for industrial applications. Temporal and spatial beam shaping was demonstrated to improve existing and enable novel applications. A very promising technology for both highly dynamic beam shaping and power scaling is the coherent combining of the beams of an array of high-power fundamental mode fibers. However, the limited number of fibers allows only limited spatial resolution of the common phase front. It is therefore favorable to work with plane or spherical common phase fronts, which generate a “point”, i.e., a diffraction pattern with a strong main lobe in the focal plane. By applying a tilt to the common phase front, points can be positioned in the focal plane with high spatial resolution. The Civan DBL 6–14 kW investigated in this work allows switching between positions of the points with 80 MHz. Sequences of points can be used to create arbitrary shapes. The time constants of points and shapes are very critical for this type of shape generation. The current paper analyzes the relevant time constants for setting points and creating shapes and relates them to time constants in laser processes. This is mandatory to deterministically influence laser processes.